Kreasi Desain Digital: Pelatihan Figma untuk Siswa SMA Wiyata Dharma - Ilhami, Mirza; Kristian Telaumbanua; Syanti Irviantina; Irpan Adiputra Pardosi; Kelvin, Kelvin (Universitas Methodist Indonesia, 2025)
In the era of Industry 4.0, the digital divide in high school education, particularly in urban areas like Medan, limits students' access to modern design tools such as Figma for user interface (UI) and user experience (UX) prototyping. This community service activity aims to bridge this gap by providing basic Figma training to 25 Class XI students at SMA Wiyata Dharma. The implementation involved a two-day interactive workshop, covering UI/UX concepts, basic tools (shapes, text, auto-layout), and wireframe/prototype creation for educational apps. Methods included lectures, demonstrations, and hands-on practice, supported by printed modules and free Figma accounts. Evaluation via pre- and post-tests (10 multiple-choice questions) showed a significant improvement from an average score of 45% to 78% (73% increase, p<0.05 via t-test), while partner satisfaction averaged 4.8/5 on a Likert scale. This confirms the hypothesis of at least 25% enhancement in UI/UX understanding, fostering digital creativity and career readiness.